(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the wisdom of Khoja Ahmed Yassavi is analyzed in terms of content and form. The images in the proverbs were analyzed and studied from the point of view of artistic skill. Formal aspects of proverbs are studied. Theoretical and analytical opinions are given on the art of Ahmad Yassavi’s wisdom. The classification of figurative and real love and its sources are given. Proverbs on the topic of love are analyzed and traditional and figurative symbols such as May, Soqi, Ashik, Mashukha, Piri Mugon are identified.